2017 IEEE Power &Amp; Energy Society General Meeting 2017
DOI: 10.1109/pesgm.2017.8273761
|View full text |Cite
|
Sign up to set email alerts
|

Active control of DC fault currents in DC solid-state transformers during ride-through operation of multi-terminal HVDC systems

Abstract: When a pole-to-pole dc fault occurs in a multiterminal HVDC system, it is desirable that the stations and dc solid-state transformers on healthy cables continue contributing to power transfer, rather than blocking. To reduce the fault current of a modular multilevel converter based dc solid-state transformer, active fault current control is proposed, where the dc and ac components of fault arm currents are regulated independently. By dynamically regulating the dc offset of the arm voltage rather than being set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…As MMCs typically use hundreds of submodules per arm in HVDC application, it is extremely time consuming to simulate the whole system using detailed switching models, which considers the switching behavior of the IGBTs/diodes. To reduce computation time and accelerate the simulation, average models are widely adopted to represent the MMC behavior [31][32][33][34][35]. It has demonstrated that such average models provide adequate accuracy for DC fault detection studies [12,13,32,33] and are thus adopted in this study.…”
Section: DC Fault Detection Of Meshed Three-terminal Hvdc Systemmentioning
confidence: 99%
“…As MMCs typically use hundreds of submodules per arm in HVDC application, it is extremely time consuming to simulate the whole system using detailed switching models, which considers the switching behavior of the IGBTs/diodes. To reduce computation time and accelerate the simulation, average models are widely adopted to represent the MMC behavior [31][32][33][34][35]. It has demonstrated that such average models provide adequate accuracy for DC fault detection studies [12,13,32,33] and are thus adopted in this study.…”
Section: DC Fault Detection Of Meshed Three-terminal Hvdc Systemmentioning
confidence: 99%
“…In Li et al, a new active fault current control strategy is developed during pole‐to‐pole DC fault conditions for multiterminal MMC based DC SST application. Control methodology is explained for AC voltage and power control mode.…”
Section: Application Areasmentioning
confidence: 99%
“…Due to modularity and scalability, modular multilevel converter (MMC) has become the most attractive converter topology for medium/high-voltage applications, especially for voltage-sourced converter high-voltage direct current transmission systems [1]. For large-scale MMC-embedded power systems, it is required to investigate dynamic performance, fault, protection, and stability [2][3][4]. Modelling of the MMC is one of the main challenges associated with the study of the large-scale MMC-based power systems.…”
Section: Introductionmentioning
confidence: 99%